Farmers' Access to Farm Programs of Bangladesh Betar: An Evaluation of Effectiveness - Mahedi Hasan , Nazrul Islam Mondal , Nurul Islam and Aminul Hoque, (Indian Journal of Extension Education, 2017)
Different forms of farm programs (FP) have been being developed and aired by Bangladesh Betar (BB) for decades tohasten the development of agriculture and the farming communities of Bangladesh. These programs are in dire need ofacademic study for in-depth evaluation to discern their effectiveness. This study was supposed to reveal the effectivenessof the FP of BB in respect of the extent to which it reaches the farmers of Bangladesh. Data and necessary informationwere collected by means of document analysis and survey methods. A sample of 465 respondents was selected forquestionnaire survey. Frequency distribution and z-test for significance test of proportions were done for data analysis. Itwas divulged that the FPs of BB were ineffectual because they failed to reach 93.33 per cent of the farmers. Radio set, aculturally unfit device was possessed by only 4.30 per cent of the farmers. Most of the farmers were accustomed tounauthorized sources (salesman and fellow farmers) of farm information. Avast majority of the respondents were insolenttowards the authorized extension agents and departments. The unconsciousness regarding the importance of farmknowledge and their mindset were the most influencing factors for listening to the FPs. Initiatives were must to change thelong cherished mindset of the farmers and culturally fit devices were to be patronized in receiving the radio FPs.